Rol del defensor público en la audiencia de legalidad de la detención y calificación de flagrancia: propuesta de creación de un instrumento de regulación a los actuaciones de los defensores públicos en la audiencia de flagrancia - Ortiz Sevilla, Chris Stefan (2015)
This research explores the different aspects to be highlighted in the performance and actions of the public defender as guarantor on equal rights and opportunity for all citizens regardless of defending enjoy a professional efficient defense of their economic, social and educational skills, and quality during the hearing of flagrancy. The specifics of the process also address flagrancy, importance and relevance today, proposing the creation of a manual action of the public defender in flagrante delicto hearing, legal tool through which the action of the public defender will empower, detailing action strategies that ensure the constitutional mandate of a defense. The proposed development of a manual action of the public defender in flagrante delicto hearing, pursues the specific guarantee optimal quality and performance in which the knowledge and professionalism of counsel at the hearing of flagrancy denote objectives, taking into account all technical and legal related to such performance, while aspects pursued with the development of the manual actuation public defender at the hearing of flagrancy better performance and performance of the administrators of justice materializing the standardization of performance public defender at the hearing of flagrancy. The audience of flagrancy has an important and relevant in the present system of Ecuadorian justice, hence the importance of ensuring a consistent performance of public defenders to ensure respect for due process and constitutional guarantees in effect, a situation which derives the need to regulate in a clear and simple way the performance of the public defender, and likewise raise the quality of the legality and therefore respect the rights of citizens.